2012
DOI: 10.1021/ja301901p
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Specific DNA Cross-Linking Triggered by Visible Light

Abstract: A new biocompatible strategy for photoinduced DNA interstrand cross-linking is presented. Methylene blue induced (1)O(2) formation triggers furan oxidation; the resulting aldehyde then rapidly reacts with complementary A or C with formation of stable adducts. Easily accessible furan modified nucleosides, a commercially available photosensitizer, and visible light irradiation constitute the necessary tools to achieve selective duplex interstrand cross-linking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 33 publications
2
83
1
1
Order By: Relevance
“…An HPLC comparison with authentic 17 confirmed that the cross-link was predominantly formed with the 6-amino group of dA at acidic pH (Figure 5A). Conversely, Figure 5B clearly shows that the cross-link was formed at the N3 atom of T ( 18 ) at alkaline pH (Figure 5B). These results suggest that the reactivity of the vinyl group of 2 is affected by the pH of the reaction medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An HPLC comparison with authentic 17 confirmed that the cross-link was predominantly formed with the 6-amino group of dA at acidic pH (Figure 5A). Conversely, Figure 5B clearly shows that the cross-link was formed at the N3 atom of T ( 18 ) at alkaline pH (Figure 5B). These results suggest that the reactivity of the vinyl group of 2 is affected by the pH of the reaction medium.…”
Section: Resultsmentioning
confidence: 99%
“…Cross-link formation is also used to maintain 3D nucleic acid structures (9–11). A variety of functional groups have also been developed to enable interstrand cross-linking, including disulfide bonds (12), benzophenone derivatives (13), carbazoles (14), quinone methides (15,16), phenylselenyl derivatives of pyrimidines (17) and furan derivatives (18). To further advance these studies, an efficient cross-linking method is still desired.…”
Section: Introductionmentioning
confidence: 99%
“…This crosslinking chemistry is based on the pronounced propensity of furans to undergo oxidative conversion to highly electrophilic ene‐1,4‐diones in an aqueous environment; these readily react with DNA and RNA nucleobases bearing exocyclic amino groups (Scheme ) 2b. 6 An attractive feature of this reaction sequence is that it can be initiated with singlet oxygen, which can be generated in situ by irradiation of photosensitisers with non‐UV light under aerobic conditions 2a. This enables spatiotemporal control of crosslinking and offers enhanced penetration depths in biological samples.…”
Section: Methodsmentioning
confidence: 99%
“…Since 1 O 2 can be generated by irradiation of photosensitizers with red light, this approach should offer a high penetration depth in complex biological samples and the absence of nucleic acid damaging photoreactions associated with UV light. This chemistry had previously been described and thoroughly characterized in the context of DNA-DNA interstrand crosslink formation and proceeds via a proposed mechanism involving a 2+4 cycloaddition of 1 O 2 to the furan, opening of the resulting ozonide, and ultimately formation of a γ-keto-enal that can build cyclic adducts with A, G, and C nucleobases (Figure 2C) (Op De Beeck and Madder, 2011, 2012). Since this represents a rather nucleic acid-selective crosslinking chemistry that targets only certain nucleobases, it could provide more detailed information on the topology of protein-nucleic acid complexes, potentially including information about the binding mode of protein motifs (backbone- or groove-interaction) and the pairing state of individual nucleobases in complexed RNA or DNA.…”
Section: Genetically Encoded Chemistries For Studying Regulatory Procmentioning
confidence: 97%